Analisis Yuridis Vaksin Covid-19 Ilegal: Perlindungan dan Penegakan Hak Kesehatan Warga Negara Indonesia: Juridical Analysis of Illegal Covid-19 Vaccines: Protection and Enforcement of Health Rights of Indonesian Citizens - Hertianto, M Rafifnafia; Maharani, Ni Putu Maetha (Fakultas Hukum Universitas Negeri Semarang, 2021)
Health rights are one of the basic rights stated in the Articles of 28H (1) Indonesia`s constitution. Covid-19 becomes an examination moment if the State can fulfil the health rights of its citizens. Some regulations have been issued to reduce coronavirus dissemination, one of them is the health ministerial regulations No. 10/2021 on the implementations of covid-19 vaccinations to the countermeasures of the covid-19 pandemic. Unfortunately, those policies become a loophole to gain profit for some irresponsible actors. A number of the abuses of vaccinations implementation cases arise along with the government effort to carry out the vaccination. The purpose of this research is to analyze the implementation of health right during pandemic through vaccination program which organized by the government and to analyze the protection of citizen’s health right to the illegal vaccine case phenomenon. This research is written by juridical normative method with law and cases approached and also use secondary data. Based on the research, the implementation of the health right through vaccination program which is organized by the government regards some principles according to Public Service Law Number 25/2009. But, there is an abuse of power in the execution stage, like illegal vaccine cases that contravene public service, equal right, balance of rights and obligations, professionalism and non discrimination principles. The executant can also be punished into multi-layer sanction such as administrative sanction and criminal sanction.